2011
DOI: 10.1103/physreva.83.042333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative model study of two-photon deterministic passive quantum logical gates

Abstract: We use the "modes of the universe" approach to study a cavity-mediated two-photon logical gate recently proposed by Koshino, Ishizaka and Nakamura. We clarify the relationship between the more commonly used input-output formalism, and that of Koshino et al., and show that some elements of this gate had been anticipated by other authors. We conclude that their proposed gate can work both in the good and bad cavity limits, provided only that the pulses are long enough. Our formalism allows us to estimate analyti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…To have φ = π/4, Koshino, Ishizaka and Nakamura derived the condition δ a = 2g 2 /κ for the detuning between the atom and the cavity, assuming implicitly that the cavity and the field were resonant. For the more general case where the field is detuned from the cavity resonance by an amount ∆, we showed in [14] that the condition to have φ = π/4 is…”
Section: The Original Kin Schemementioning
confidence: 99%
“…To have φ = π/4, Koshino, Ishizaka and Nakamura derived the condition δ a = 2g 2 /κ for the detuning between the atom and the cavity, assuming implicitly that the cavity and the field were resonant. For the more general case where the field is detuned from the cavity resonance by an amount ∆, we showed in [14] that the condition to have φ = π/4 is…”
Section: The Original Kin Schemementioning
confidence: 99%
“…By using a -type three-level system as an emitter in waveguide QED, we can enhance the probability that the input photon induces the Raman transition and accordingly switches the quantum state of the system. In particular, it has been theoretically revealed that this probability may reach unity when the following conditions are satisfied: (i) the system is coupled to the waveguide field in reflection geometry; and (ii) the two radiative decay rates from the top level of the system are identical [23][24][25][26][27][28]. Then, the input photons are never reflected coherently and the amplitude of the reflected wave vanishes accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this phenomenon as the impedance matching by a system, in analogy with properly terminated electric circuits. Such impedance-matched systems are attractive for quantum information processing, since the expected deterministic quantum dynamics is applicable to quantum memories [24][25][26], single-photon transistors [27,28], photon sorters [29], photon-photon gates [24-26, 30, 31] and single-photon detectors in microwave domain [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The charm of such impedance-matched systems is the deterministic electronic dynamics induced by single photons, which enables novel quantum technologies. Based on such Λ systems, single-photon transistors, quantum memories, and optical quantum gates have been theoretically proposed [11][12][13][14][15][16].In superconducting qubits, we use several discrete levels formed at the bottom of the anharmonic potential as an artificial atom. We usually make the potential symmetric in order to suppress dephasing.…”
mentioning
confidence: 99%